High cure rates in Burkitt lymphoma and leukemia: a Northern Italy Leukemia Group study of the German short intensive rituximab-chemotherapy program - Tamara Intermesoli; Alessandro Rambaldi; Giuseppe Rossi; Federica Delaini; Claudio Romani; Enrico Maria Pogliani; Chiara Pagani; Emanuele Angelucci; Elisabetta Terruzzi; Alessandro Levis; Vincenzo Cassibba; Daniele Mattei; et al. (Haematologica, 2013)
We evaluate the long-term results of a prospective clinical study enrolling more than 100 adult patients with Burkitt lymphoma/leukemia. Depending on extent of disease, treatment consisted of six to eight rituximab infusions and four to six courses of intensive chemotherapy (attenuated in patients aged >55 years) with high-dose methotrexate, fractionated ifosfamide/cyclophosphamide, other drugs in rotation, and intrathecal chemoprophylaxis. One-hundred five patients were treated (median age 47 years, range 17–78 years); 48% had Burkitt leukemia, 25% were older than 60 years, 37% had an Eastern Cooperative Oncology Group performance score >1, and 14% were positive for human immunodeficiency virus. The complete response rate and 3-year overall and disease-free survival rates were 79%, 67% and 75%, respectively, ranging from 100% to 45% for survival (P=0.000) and from 100% to 60% for disease-free survival (P=0.01) in patients with low, intermediate and high adapted International Prognostic Index scores. In multivariate analysis, only age (≤ versus >60 years) and performance status (0–1 versus >1) retained prognostic significance, identifying three risk groups with overall and disease-free survival probabilities of 88% and 87.5%, 57% and 70.5%, 20% and 28.5% (P=0.0000 and P=0.0001), respectively. The relapse rate was only 7% in patients treated with an intercycle interval ≤25 days. This regimen achieved 100% curability in patients with low adapted International Prognostic Index scores (21% of total), and very close to 90% in patients aged ≤60 years with performance score 0–1 (48% of total). Rapid diagnosis of Burkitt lymphoma/leukemia with prompt referral of patients to prevent clinical deterioration, and careful supervision of treatment without chemotherapy delay can achieve outstanding therapeutic results. ClinicalTrials.gov ID, NCT01290120